Development of E-Digital Archives of the Faculty of Economics, Universitas Negeri Semarang - Rohmawati Rohmawati; Ahmad Saeroji; Januharto Partono; Moch Faizal Rachmadi (Universitas Negeri Semarang, 2023)
This research aims to develop Static and Inactive Archives at the Faculty of Economics into E-Digital Archives and conduct monitoring and evaluation. This study uses a development model (Research and Development). Monitoring and evaluation is carried out to find out the ease of implementing input and what obstacles are experienced when inputting E-Digital Archives. The results of the study show that the condition of archive management at the Faculty of Economics, especially static archives and inactive archives, is still in the process of being reorganized. The FE Record Center has organized manual archives consisting of cupboard A for accounting and financial records for 2013-2020, cupboard B for student and academic archives, cupboard C for general and personnel archives and mixed archives. For the development of e-digital archives, the results of monitoring and evaluation in the UNNES Digital Archive System show that up to October 31, 2022, 1,452 letters/archives have been uploaded, divided into dynamic, inactive and FE UNNES static archives